2004
DOI: 10.1212/01.wnl.0000144276.29988.c3
|View full text |Cite
|
Sign up to set email alerts
|

Ceruloplasmin gene variations and substantia nigra hyperechogenicity in Parkinson disease

Abstract: Detection of sequence variations in a single Parkinson disease (PD) patient or associated with the ultrasound marker for increased substantia nigra iron levels and the presence of ceruloplasmin (Cp) immunoreactivity in Lewy bodies underline a suspected role for Cp in the pathogenesis of PD. Further functional analyses are warranted to investigate whether these variations are causally linked to the complex pathogenesis of PD in a subset of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 34 publications
5
92
1
3
Order By: Relevance
“…In this study, five unique missense variations were identified including, a single incidence of I63T, D554E, which correlated with PD and positive ultrasound for increased substantia nigra iron levels, and R793H, which was linked to increased levels of iron levels in individuals with PD and their age/ethnic-matched individuals. This study also showed that Cp localizes with the Lewy bodies associated with the pathology of PD (134). In further investigation, the I63T mutant Cp isoform was expressed at half the normal level and displayed a distinct decrease in ferroxidase activity in vivo.…”
Section: Iron Regulation and Neurodegenerationsupporting
confidence: 58%
See 1 more Smart Citation
“…In this study, five unique missense variations were identified including, a single incidence of I63T, D554E, which correlated with PD and positive ultrasound for increased substantia nigra iron levels, and R793H, which was linked to increased levels of iron levels in individuals with PD and their age/ethnic-matched individuals. This study also showed that Cp localizes with the Lewy bodies associated with the pathology of PD (134). In further investigation, the I63T mutant Cp isoform was expressed at half the normal level and displayed a distinct decrease in ferroxidase activity in vivo.…”
Section: Iron Regulation and Neurodegenerationsupporting
confidence: 58%
“…A study of 176 individuals with PD and 180 control subjects who underwent transcranial ultrasound to reveal elevated substantia nigra iron levels, subsequently were evaluated for mutations in the Cp gene (134). In this study, five unique missense variations were identified including, a single incidence of I63T, D554E, which correlated with PD and positive ultrasound for increased substantia nigra iron levels, and R793H, which was linked to increased levels of iron levels in individuals with PD and their age/ethnic-matched individuals.…”
Section: Iron Regulation and Neurodegenerationmentioning
confidence: 99%
“…However, less is known about the cause of low serum CP levels in PD patients. In this study, we found that the CP gene in The frequency of D544E differed significantly between PD patients and controls [24] . Another study by Castiglioni CP gene variants seemed to be associated with PD in this study [25] .…”
Section: No Copy Number Variations Of the Cp Gene In Pd Patientsmentioning
confidence: 52%
“…Increased echogenicity of SNc can be documented in 90% of PD patients by transcranial ultrasound, suggestive of iron accumulation [8]. PD patients with Cp missense mutations were found to have reduced Cp levels and ferroxidase activity [9].…”
Section: Discussionmentioning
confidence: 99%